Restorative Justice Approach in Crime of Humiliation Through Social Media - Fithri, Beby Suryani; Wahyuni, Windy Sri (Faculty of Law, Pembangunan Nasional Veteran Jakarta University, 2021)
The restorative justice approach is a diversion in the handling of criminal acts which in the criminal justice procedure are centered on imposing criminal sanctions which are transferred to a communication and mediation process that presents the perpetrators, victims, families of the perpetrators/victims, and other related parties to come together to realize a form of agreement. for the handling of criminal acts that are fair and proportional to the victims who are harmed and the perpetrators by prioritizing repairs such as initial conditions and restoring a harmonious interaction model in society. It is this restorative justice approach that will be used in the investigation, investigation and examination stages in courts of insults, considering that the enforcement of criminal law against insult cases that occur in the community has not given satisfactory results. The regulation of defamation offenses whether carried out offline or online with social media refers to the provisions of the Criminal Code (KUHP) and the Information and Electronic Transactions Law, which in these two provisions contain criminal sanctions against the perpetrators. The purpose of the restorative justice approach in dealing with insults offenses is the restoration of victims who suffered as a result of the humiliation by providing compensation, imposing social work on the perpetrators and matters mutually agreed upon by the parties.